A multi-national comparison of meat eaters' attitudes and expectations for burgers containing beef, pea or algae protein. (July 2021) - Michel, Fabienne; Knaapila, Antti; Hartmann, Christina; Siegrist, Michael
Highlights: Pea and algae burger expected to be less tasty than beef burger. Pea and algae burger expected to be healthy and environmentally friendly. Pea and algae as promising protein sources for new meat alternatives. Burger expectation influenced by meat commitment and food neophobia. Participants expressed negative attitudes towards vegetarian and vegan lifestyles. Abstract: Within recent years, demand as well as supply of products to replace meat, so called meat alternatives, have increased. For future products, new plant-based protein sources are of high interest. Protein from pea and especially from algae provide huge potential for human nutrition as well as for the environment. To provide insight on consumers' opinions on the development of new meat alternatives, this study investigated consumers' opinions of pea and algae burgers compared to the traditional beef burger in terms of taste, health, and environmental friendliness. It has also explored the influence of factors such as meat commitment, food neophobia, and the attitude towards vegetarians and vegans; it has then compared the findings between three European countries with different culinary backgrounds. The online survey was conducted with meat-eating participants from Germany (N = 567), France (N = 605), and the United Kingdom (N = 562). Participants in all three countries expected pea and algae burgers to be less tasty, but healthier and more environmentally friendly compared to the beef burger. Expectations of taste, health, and environmental friendliness of pea and algae burgers were negatively influenced by higher levels of meat commitment, more negative attitudes towards vegetarian and vegan lifestyles, and higher food neophobia. Although the attitudes towards vegetarian lifestyles were generally negative, pea and algae emerged as promising protein sources because of their favorable health and environmental friendliness expectations. Nevertheless, negative taste expectations and attitudes towards meat-free diets remain a challenge for the adoption of more plant-based diets.